Investigating key function-altering mutations in asparaginyl endopeptidase butelase 2 - Ng, Jia Hao (2018)
Butelase 2 is a natural protease derived from Clitoria ternatea, the same plant where the fastest known AEP ligase butelase 1 was discovered. The fundamental function of AEP ligases is to macrocyclize cyclotides to achieve ultra-stable forms and new biological functions beneficial to drug discovery and biopharmaceutics. To understand how butelase 1 can achieve the gold standard of macrocyclization, closely-related homologs like butelase 2 were examined. In this study, butelase 2 was mutagenized at specific key residues. A total of 3 different mutants were generated, with one, ‘G252V’, exhibiting efficient ligase capability. The butelase 2 variants were purified, and their enzymatic activation and activity test conditions were optimized for kinetic studies. G252V attained catalytic efficiencies of up to 207,046 M-1s-1, which is a significant increase from the wildtype. We have demonstrated that single amino acid mutations, like glycine to valine in the case of G252V, can successfully convert a protease into a ligase. The discovery of the first efficient butelase 2 ligase marks an important milestone in the understanding of butelase 1’s ligation mechanism. This project also provides greater insight into characterization and optimization strategies for the generation of active butelase 2 variants.